Is the whole story of coastal change being told by 2D shoreline erosion rates? - Christoff, Katie N (East Carolina University, 2022)
Shoreline location has often been gathered from orthoimagery to assess the 2D planimetric erosion or accretion and thereby is used as proxy for coastal evolution and to manage coastal environments. Missing in the 2D measures of shoreline location are the coastal morphodynamics. Topography is constantly changing inward of the wet/dry line and accounts for the elevation changes throughout the year in the beach, dune, back barrier and/or coastal cliff. An understanding of the space-time changes in topography is critical to assessing the broader risks associated with shoreline erosion/accretion, coastal flooding and change to coastal habitat, infrastructure, and housing. This study examines the relationships between traditional 2D measures of coastal change and the juxtaposed 3D morphodynamics in coastal settings. While it was anticipated that areas of accretion would show an increase in volume and/or elevation while areas of erosion would illustrate the opposite, that was not the case at all locations. Morphodynamics do show some consistent trends but not strong relationships with the 2D shoreline change data. Further analyses are needed to tease out the complex relations.
Keywords: Shoreline, Erosion, Outer Banks, NC